2009
DOI: 10.1101/gr.097501.109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the fungal pathogens Candida dubliniensis and Candida albicans

Abstract: Candida dubliniensis is the closest known relative of Candida albicans, the most pathogenic yeast species in humans. However, despite both species sharing many phenotypic characteristics, including the ability to form true hyphae, C. dubliniensis is a significantly less virulent and less versatile pathogen. Therefore, to identify C. albicans-specific genes that may be responsible for an increased capacity to cause disease, we have sequenced the C. dubliniensis genome and compared it with the known C. albicans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
243
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(254 citation statements)
references
References 70 publications
(88 reference statements)
9
243
0
2
Order By: Relevance
“…It has been suggested that C. dubliniensis is more capable of developing antifungal resistance (e.g., to azoles) than C. albicans. 9,12,14 This feature of C. dubliniensis may be associated with its prevalence in AIDS patients, who are often subjected to antifungal treatments. Our results showing the upregulated expression of a number of ergosterol biosynthesis genes in gray cells of C. dubliniensis provide a potential explanation for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that C. dubliniensis is more capable of developing antifungal resistance (e.g., to azoles) than C. albicans. 9,12,14 This feature of C. dubliniensis may be associated with its prevalence in AIDS patients, who are often subjected to antifungal treatments. Our results showing the upregulated expression of a number of ergosterol biosynthesis genes in gray cells of C. dubliniensis provide a potential explanation for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,12 Epidemiological studies indicate that C. dubliniensis is primarily associated with human immunodeficiency virus (HIV)-infected patients. [6][7][8][9] A number of comparative genomic and phenotypic studies of C. albicans and C. dubliniensis have been performed in the previous 2 decades, [12][13][14][15] but what underlying mechanisms or biological characteristics underlying the differences between the 2 species in epidemiology, virulence, and the ability to develop antifungal resistance remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Except for Lodderomyces elongisporus, the other five species are all pathogenic and often isolated from clinical sources. The genome sequence of Candida dubliniensis, a closely related species of C. albicans, has also been sequenced by Jackson et al [6]. Comparative analysis of the genome sequences of these pathogenic and non-pathogenic species not only identifies a lot of new genes, but also a number of species-specific virulence factors.…”
Section: Comparative Genome Sequence Analysismentioning
confidence: 99%
“…Comparative analysis of the genome sequences of these pathogenic and non-pathogenic species not only identifies a lot of new genes, but also a number of species-specific virulence factors. The pathogenic Candida species show significant expansion of several gene families including those encoding cell wall, secreted and transporter proteins [6]. For example, the Als adhesins, which are associated with virulence in C. albicans, are enriched in pathogenic species but not found in non-pathogenic species like Saccharomyces cerevisiae.…”
Section: Comparative Genome Sequence Analysismentioning
confidence: 99%
“…In biology, genome comparison is used for gene annotation, phylogenetic studies, and even vaccine design [12,2,8]. Many bioinformatics programs for whole genome comparison involve a fragment chaining step, which seeks to maximize the total length of the chained fragments (eg, [7]).…”
Section: Introductionmentioning
confidence: 99%